A heat-induced in-situ grafting fluorine-containing copolymer coating magnesium alloy stent and a preparation method and application thereof

CN122687200BActive Publication Date: 2026-10-20CHENGDU MINSHAN CHUANGZHI BIOMATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611177876.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-20
Estimated Expiration
2046-08-05

AI Technical Summary

Technical Problem

[0005]为了解决上述技术问题,本发明的目的是提供一种热引发原位接枝含氟共聚涂层镁合金支架及其制备方法和应用,以解决现有镁合金支架涂层性能较差的问题

Benefits of technology

本发明通过碱热羟基化在镁合金表面引入羟基位点,通过含双键硅烷引入可聚合界面,再在无水或低水薄液层条件下使短氟链甲基丙烯酸酯、可降解多官能甲基丙烯酸酯和少量含活性官能团甲基丙烯酸酯经热引发自由基原位共聚,形成直接与支架表面共价连接的单一交联含氟共聚网络层。因此,本发明的镁合金支架包括镁合金支架基体、形成于镁合金支架基体表面的碱热羟基化层、与碱热羟基化层缩合连接的含碳碳双键硅烷偶联层,以及由热引发自由基原位共聚形成并与含碳碳双键硅烷偶联层共价连接的含氟共聚涂层,含氟共聚涂层为直接接枝于支架表面的单一共聚网络层,并非由预制链式可降解聚合物形成的独立聚合物连接层,也并非在独立聚合物连接层外另行涂覆的抗腐蚀聚合物层。本发明可进一步接枝抗凝、促内皮化或抗炎分子的功能化平台,使涂层在延缓镁合金早期腐蚀的同时,保留后续生物功能化空间。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122687200B_ABST
    Figure CN122687200B_ABST
Patent Text Reader

Abstract

The application discloses a kind of hot initiation in-situ grafting fluorine-containing copolymer coating magnesium alloy stent and its preparation method and application, it is related to medical material coating preparation technical field.The method includes the following steps: substrate pretreatment;Carry out alkali heat reaction;It is placed in carbon-carbon double bond silane coupling agent solution, carries out condensation reaction;It is immersed in hot initiation monomer composition, carries out hot initiation free radical in-situ copolymerization, and hot initiation in-situ grafting fluorine-containing copolymer coating magnesium alloy stent is prepared.The fluorine-containing copolymer coating of the application is single copolymer network layer directly grafted on the surface of stent, not the independent polymer connecting layer formed by pre-made chain degradable polymer, nor the anticorrosion polymer layer coated outside the independent polymer connecting layer.The application can further graft anticoagulation and other functionalization platforms, so that the coating can delay the early corrosion of magnesium alloy while retaining subsequent biological functionalization space.The application solves the problem of poor performance of existing magnesium alloy stent coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical material coating technology, specifically to a thermally initiated in-situ grafted fluorine-containing copolymer coated magnesium alloy scaffold, its preparation method, and its application. Background Technology

[0002] Magnesium and magnesium alloys possess good biodegradability, low elastic modulus, and high specific strength, making them promising candidates for biodegradable vascular stents, orthopedic implants, and other temporary support implants. Magnesium alloy implants can gradually degrade in bodily fluids and, theoretically, can be absorbed by the body after tissue repair or vascular remodeling, thus reducing the risks of chronic inflammation, late-stage thrombosis, restenosis, or long-term foreign body reactions associated with long-term permanent metal implants. However, magnesium alloys corrode rapidly in chloride-containing physiological environments, easily leading to hydrogen release, local pH elevation, and Mg2+ degradation. 2+ Issues such as rapid release and insufficient early mechanical support exist. For vascular stents, excessively rapid early degradation leads to a rapid decrease in radial support force, damage to stent structural integrity, and may affect the endothelialization process. Therefore, surface modification of magnesium alloy stents and the construction of stable and controllable degradation-resistant anti-corrosion functional coatings are among the key technologies in the development of medical magnesium alloy stents.

[0003] Existing surface modification technologies for magnesium alloy scaffolds mainly include chemical conversion coatings, micro-arc oxidation films, fluorinated layers, biodegradable polymer coatings, silane coupling layers, inorganic-organic hybrid coatings, and drug-loaded composite coatings. Some of these methods use silane coupling agents as a base layer, then coat pre-prepared PLA (polylactic acid), PLGA (polylactic acid-glycolic acid copolymer), PCL (polycaprolactone), PTMC (polytrimethylene carbonate), or their copolymers using spin coating, dip coating, or spray coating. These coatings typically rely on coating to form a film, resulting in significant thickness, which makes them prone to cracking, warping, or localized peeling during scaffold compression and expansion. Other methods employ multi-layer structures. For example, a silane transition layer is first formed, followed by a chain-like biodegradable polymer connecting layer, and finally, a corrosion-resistant polymer layer or an outer bioactive layer is constructed. While these approaches can improve coating adhesion and functional integration, they involve multiple structural layers and complex preparation steps. Furthermore, mismatches in degradation rates, mechanical compliance, and interfacial bonding strength between layers can lead to interfacial failure during stent clamping, delivery, expansion, or blood flow flushing. In addition, existing fluorinated anti-corrosion coatings are primarily used on aluminum alloys, steel, or other engineering metal surfaces. A common approach involves using fluorinated methacrylates with non-degradable crosslinking agents to form a low surface energy anti-corrosion coating. This type of system may not be suitable for biodegradable magnesium alloy stents, as medical stents require coatings that can both delay early corrosion and avoid forming excessively thick, brittle, or permanently non-degradable barriers. Some hydrogel-based approaches incorporate MPC (2-methacryloyloxyethylphosphorylcholine), GMA (glycidyl methacrylate), polyarginine, selenocysteine, or NO-releasing systems, focusing on anticoagulation and catalytic NO release.

[0004] Therefore, there is a need to develop a thin, uniform, covalently grafted, blood flow-resistant, and further functionalizable surface coating suitable for three-dimensional mesh magnesium alloy scaffolds. This coating should avoid relying on pre-fabricated polymer thick coatings or independent chain-like biodegradable polymer bonding layers, and instead achieve a strong interfacial bond through in-situ copolymerization of polymerizable sites on the surface with the monomer system. Summary of the Invention

[0005] To address the aforementioned technical problems, the present invention aims to provide a thermally initiated in-situ grafted fluorine-containing copolymer coated magnesium alloy scaffold, its preparation method, and its application, thereby solving the problem of poor coating performance of existing magnesium alloy scaffolds.

[0006] The technical solution of this invention to solve the above-mentioned technical problems is as follows: A method for preparing a thermally initiated in-situ grafted fluorine-containing copolymer coated magnesium alloy scaffold includes the following steps: (1) The magnesium alloy support substrate is pretreated to obtain a pretreated magnesium alloy support; (2) The pretreated magnesium alloy scaffold obtained in step (1) is placed in an alkaline solution for alkaline-thermal reaction, then cleaned and dried to obtain a hydroxylated magnesium alloy scaffold. (3) The hydroxylated magnesium alloy scaffold obtained in step (2) is placed in a carbon-carbon double bond silane coupling agent solution to carry out a condensation reaction, and then cleaned and cured to obtain a double bond silane modified magnesium alloy scaffold. (4) The magnesium alloy scaffold with double bond silane modified in step (3) is immersed in the thermally initiated monomer composition to load a thin liquid layer on its surface. Then, thermally initiated free radical in-situ copolymerization is carried out, followed by cleaning and drying to obtain a thermally initiated in-situ grafted fluorine copolymer coated magnesium alloy scaffold. The thermally initiated monomer composition consists of total monomers, thermal initiators and solvents. The total monomers are C1-C6 fluoroalkyl methacrylates, degradable or hydrolyzable polyfunctional methacrylates and post-modified functional monomers.

[0007] The beneficial effects of this invention are as follows: This invention introduces hydroxyl sites on the surface of a magnesium alloy through alkaline thermal hydroxylation, introduces a polymerizable interface through a silane containing double bonds, and then, under anhydrous or low-water thin-layer conditions, thermally initiated free radical in-situ copolymerizes short-chain fluorinated methacrylate, biodegradable polyfunctional methacrylate, and a small amount of methacrylate containing active functional groups to form a single crosslinked fluorinated copolymer network layer directly covalently bonded to the scaffold surface. Therefore, the magnesium alloy scaffold of this invention comprises a magnesium alloy scaffold substrate, an alkaline thermal hydroxylation layer formed on the surface of the magnesium alloy scaffold substrate, a carbon-carbon double-bonded silane coupling layer condensed and bonded to the alkaline thermal hydroxylation layer, and a fluorinated copolymer coating formed by thermally initiated free radical in-situ copolymerization and covalently bonded to the carbon-carbon double-bonded silane coupling layer. The fluorinated copolymer coating is a single copolymer network layer directly grafted onto the scaffold surface, not an independent polymer connecting layer formed by pre-prepared chain-like biodegradable polymer, nor a corrosion-resistant polymer layer separately coated outside the independent polymer connecting layer. This invention can further graft functional platforms of anticoagulation, endothelialization, or anti-inflammatory molecules, so that the coating can delay the early corrosion of magnesium alloys while retaining the space for subsequent biofunctionalization.

[0008] Based on the above technical solution, the present invention can be further improved as follows: Furthermore, in step (1), the magnesium alloy stent is a coronary stent, peripheral vascular stent, biliary stent, urethral stent, orthopedic support structure or neurointervention stent made of the following materials: Mg-Zn-Ca series, Mg-Y-RE series, WE43, Mg-Nd-Zn-Zr, AZ31 or AZ91.

[0009] Furthermore, in step (1), electrochemical polishing or chemical polishing is performed first, followed by ultrasonic cleaning with ethanol solution, deionized water and ethanol in sequence, followed by nitrogen blowing and vacuum drying to complete the pretreatment process.

[0010] Furthermore, in step (1), the surface roughness Ra of the pretreated magnesium alloy support is 10 nm-300 nm.

[0011] Furthermore, in step (2), the alkaline solution is at least one of NaOH solution, KOH solution and LiOH solution.

[0012] Furthermore, in step (2), the concentration of the alkaline solution is 0.05 mol / L to 2 mol / L.

[0013] Furthermore, in step (2), the concentration of the alkaline solution is 0.2 mol / L to 1 mol / L.

[0014] Furthermore, in step (2), the alkaline heat reaction is carried out at 60℃-120℃ for 0.5h-12h.

[0015] Furthermore, in step (2), the alkaline heat reaction is carried out at 85℃-105℃ for 1h-4h.

[0016] Furthermore, in step (2), a salt is added to the alkaline solution and then an alkaline-thermal reaction is carried out. The salt is at least one of borate, carbonate, lactate and gluconate, and the concentration of the salt in the alkaline solution is 0.001 mol / L-0.2 mol / L.

[0017] The beneficial effects of adopting the above-mentioned further technical solution are: adding salt can control the grain size, roughness and density of the surface hydroxylation layer.

[0018] Furthermore, in step (2), deionized water and ethanol are used for cleaning in sequence.

[0019] Furthermore, in step (2), the product is vacuum dried at 40℃-80℃ for 0.5h-4h.

[0020] Furthermore, in step (2), the product is vacuum dried at 60°C for 1 hour.

[0021] Furthermore, in step (3), the carbon-carbon double bond silane coupling agent is 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane or allyltriethoxysilane.

[0022] Furthermore, in step (3), the carbon-carbon double bond silane coupling agent is 3-methacryloyloxypropyltrimethoxysilane.

[0023] Furthermore, in step (3), the concentration of the carbon-carbon double bond silane coupling agent solution is 0.5vt%-5vt.

[0024] Furthermore, in step (3), the solvent of the carbon-carbon double bond silane coupling agent solution is a mixture of ethanol and water, or a mixture of isopropanol and water, or a mixture of ethanol, water and acetic acid.

[0025] Furthermore, in step (3), the pH of the carbon-carbon double bond silane coupling agent solution is adjusted to 3.5-5.5 with acetic acid, pre-hydrolyzed for 10-60 minutes, and then subjected to condensation reaction.

[0026] Furthermore, in step (3), the condensation reaction is carried out at 20℃-50℃ for 20min-180min.

[0027] Furthermore, in step (3), ethanol is used for cleaning.

[0028] Furthermore, in step (3), the product is cured at 60℃-120℃ for 10min-120min.

[0029] Further, in step (4), the C1-C6 fluoroalkyl methacrylate is at least one of 2,2,2-trifluoroethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, and 2,2,3,3,4,4,5,5-octafluoropentyl methacrylate; or, the C1-C6 fluoroalkyl methacrylate comprises 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, and also comprises at least one of 2,2,2-trifluoroethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, and 2,2,3,3,4,4,5,5-octafluoropentyl methacrylate.

[0030] Furthermore, in step (4), the C1-C6 fluoroalkyl methacrylate is 2,2,2-trifluoroethyl methacrylate and / or 2,2,3,3-tetrafluoropropyl methacrylate.

[0031] Further, in step (4), the degradable or hydrolyzable polyfunctional methacrylate is at least one of polycaprolactone dimethacrylate, polycarbonate dimethacrylate, polylactic acid dimethacrylate, acetal dimethacrylate, disulfide dimethacrylate, succinate dimethacrylate, phosphate dimethacrylate, and glycerol dimethacrylate succinate.

[0032] Furthermore, in step (4), the post-modifiable functional monomer is methacrylic acid, 2-hydroxyethyl methacrylate, N-hydroxysuccinimide methacrylate, propargyl methacrylate, azidoethyl methacrylate, maleimide methacrylate, or protected amino methacrylate.

[0033] Furthermore, the protected amino methacrylate is N-Boc-2-aminoethyl methacrylate, N-Fmoc-2-aminoethyl methacrylate, or N-Boc-aminopropyl methacrylate.

[0034] Furthermore, in step (4), the post-modifiable functional monomer is methacrylic acid.

[0035] Furthermore, in step (4), the thermal initiator is azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, dilauryl peroxide, or tert-butyl peroxyneoplastate.

[0036] Furthermore, in step (4), the thermal initiator is azobisisobutyronitrile or azobisisoheptanenitrile.

[0037] Furthermore, in step (4), the solvent is at least one of ethanol, isopropanol, ethyl acetate, acetone, tetrahydrofuran, 1,4-dioxane, trifluoroethanol and hexafluoroisopropanol.

[0038] Furthermore, in step (4), the molar ratio of C1-C6 fluoroalkyl methacrylate, degradable or hydrolyzable polyfunctional methacrylate, and post-modifiable functional monomer is (40-95): (1-30): (0.1-20).

[0039] Furthermore, in step (4), the molar ratio of C1-C6 fluoroalkyl methacrylate, degradable or hydrolyzable polyfunctional methacrylate, and post-modifiable functional monomer is (55-85): (3-15): (1-8).

[0040] Furthermore, in step (4), the mass of the thermal initiator is 0.01%-3% of the total monomer weight.

[0041] Furthermore, in step (4), the mass of the thermal initiator is 0.05%-1% of the total monomer weight.

[0042] Furthermore, in step (4), the concentration of total monomers in the solvent is 1wt%-60wt%.

[0043] Furthermore, in step (4), the concentration of total monomers in the solvent is 5wt%-30wt%.

[0044] Furthermore, in step (4), the thickness of the thin liquid layer is 0.1 μm-20 μm.

[0045] Furthermore, in step (4), thermally initiated free radical in situ copolymerization is carried out in an inert atmosphere or a low-oxygen environment.

[0046] Furthermore, in step (4), when thermally initiated free radical in situ copolymerization is carried out, polymerization is performed at 40℃-90℃ for 0.5h-12h.

[0047] Furthermore, in step (4), when performing thermally initiated free radical in situ copolymerization, the prepolymerization is carried out at 40℃-55℃ for 10min-60min, and then the main polymerization is carried out at 60℃-75℃ for 1h-6h.

[0048] Furthermore, in step (4), the solvents are used to clean the product in sequence with ethyl acetate, ethanol and isopropanol, for 10 min to 30 min for each solvent.

[0049] Further, repeat the cleaning process 2-3 times.

[0050] Furthermore, in step (4), the product is vacuum dried at 40°C for 12 hours.

[0051] Furthermore, in step (4), the coating thickness of the thermally initiated in-situ grafted fluorine copolymer coated magnesium alloy scaffold is 0.1μm-10μm.

[0052] Furthermore, in step (4), the coating thickness of the thermally initiated in-situ grafted fluorine copolymer coated magnesium alloy scaffold is 0.3μm-6μm.

[0053] The present invention also provides a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold, which is prepared by the above-mentioned method for preparing a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold.

[0054] The present invention also provides the application of the above-mentioned thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold in the preparation of magnesium alloy scaffolds.

[0055] The present invention has the following beneficial effects: (1) The present invention adopts thermally initiated free radical in-situ copolymerization, and the heat can be uniformly applied to the inner surface, outer surface, side wall and corner area of ​​the three-dimensional mesh scaffold, which is more suitable for full surface polymerization of complex scaffold structures than simple photoinitiation.

[0056] (2) The present invention provides polymerizable sites on the surface through a silane coupling layer containing double bonds, so that the carbon-carbon double bonds in the silane layer participate in copolymerization to form a fluorine-containing copolymer network (magnesium alloy surface-Mg-O-Si-copolymer network) covalently connected to the magnesium alloy surface, which is different from ordinary physical coating or simple silane primer.

[0057] (3) The fluorinated copolymer coating of the present invention is a single copolymer network layer, which does not contain an independent polymer linking layer formed by pre-made chain degradable polymer, and does not require an additional anti-corrosion polymer layer to be coated outside the independent polymer linking layer, thus reducing the risk of interlayer interface failure.

[0058] (4) The present invention uses C1-C6 short fluorine chain methacrylate to construct a water-blocking and chlorine-blocking main network, which can reduce the penetration of water molecules and chloride ions into the surface of magnesium alloy and delay the early corrosion of magnesium alloy.

[0059] (5) The present invention introduces degradable or hydrolyzable polyfunctional methacrylates as crosslinking units to form mild crosslinking and provide controllable degradation sites, thereby improving the resistance to erosion, swelling and expansion and the integrity after expansion, while avoiding the formation of an overly persistent non-degradable inert barrier.

[0060] (6) The coating thickness of the present invention is preferably 0.3μm-6μm, which is more suitable for stent gripping, delivery and balloon expansion process than traditional thick polymer coatings, and can reduce the risk of cracking and peeling.

[0061] (7) The present invention provides secondary grafting sites through a small number of functional monomers. The coating surface can provide post-modification reaction sites through carboxyl, hydroxyl, NHS ester, azide, alkynyl, maleimide or epoxy groups. Anticoagulant, endothelialization, anti-inflammatory or antioxidant molecules can be further grafted according to different clinical needs, which has platform expansion value.

[0062] (8) The present invention performs thermally initiated in-situ polymerization in anhydrous or low-water thin liquid layers, which reduces the uncontrolled corrosion of magnesium alloys in the aqueous phase during the polymerization stage and reduces the risk of bulk polymerization forming non-grafted thick films. Attached Figure Description

[0063] Figure 1 A schematic diagram of the structure of a magnesium alloy support surface thermally initiated in-situ grafted with a fluorinated copolymer coating; Figure 2 This is a schematic diagram of the preparation process in Example 1; Figure 3 The infrared spectrum of the coating obtained in Example 1; Figure 4 This is a scanning electron microscope image of the hydroxylated magnesium alloy scaffold of Example 1 after compression and balloon dilation; Figure 5 This is a scanning electron microscope image of the double-bonded silane-modified magnesium alloy scaffold of Example 1 after compression and balloon dilation; Figure 6 This is a scanning electron microscope image of the thermally initiated in-situ grafted fluorine copolymer-coated magnesium alloy scaffold of Example 1 after compression and balloon dilation; Figure 7 The absorbance values ​​are those of the cell culture solutions of the scaffold in Example 1, the scaffold in Comparative Example 1, and the bare scaffold. Detailed Implementation

[0064] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer should be followed. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0065] Hereinafter referred to as: 2,2,2-Trifluoroethyl methacrylate (TFEMA), 2,2,3,3-Tetrafluoropropyl methacrylate (TFPMA), polycaprolactone dimethacrylate (PCLDMA), methacrylic acid (MAA), and azobisisobutyronitrile (AIBN).

[0066] Example 1: A thermally initiated in-situ grafted fluorine-containing copolymer coated magnesium alloy scaffold, the preparation method of which includes the following steps: (process flow is available in...) Figure 2 ) (1) The magnesium alloy support substrate (WE43) was electrochemically polished, and then ultrasonically cleaned with ethanol solution, deionized water and ethanol in sequence for 8 minutes each time. After being dried with nitrogen, it was vacuum dried to complete the pretreatment process and obtain the pretreated magnesium alloy support. (2) The pretreated magnesium alloy support obtained in step (1) was placed in an alkaline solution (0.5 mol / L NaOH solution) and subjected to alkaline heat reaction at 95°C for 2 hours to form a hydroxylated layer on the surface. It was then washed with deionized water and ethanol in sequence and vacuum dried at 60°C for 1 hour to obtain a hydroxylated magnesium alloy support. (3) The hydroxylated magnesium alloy scaffold obtained in step (2) was placed in a carbon-carbon double bond silane coupling agent solution and condensed at 25°C for 60 min. Then it was washed with ethanol and cured at 90°C for 30 min to obtain a magnesium alloy scaffold modified with double bond silane. The carbon-carbon double bond silane coupling agent solution was prepared by the following method: a 1 wt% 3-methacryloyloxypropyltrimethoxysilane solution was prepared, the solvent being a mixture of ethanol and water with a volume ratio of 90:10, the pH was adjusted to 4.5 with acetic acid, and pre-hydrolyzed for 30 min. (4) Immerse the magnesium alloy scaffold modified with double-bonded silane obtained in step (3) into the thermally initiated monomer composition for 3 min. After removal, purge with nitrogen and rotate the control film to load a thin liquid layer on its surface. Then place it in a nitrogen-protected environment for thermally initiated free radical in-situ copolymerization (prepolymerize at 50°C for 30 min, then perform main polymerization at 65°C for 3 h) to allow the surface double-bonded silane to undergo thermally initiated free radical in-situ copolymerization with the monomer (see Figure 1 The process involves a magnesium alloy substrate, an alkaline-thermal hydroxylation layer, a silane coupling layer containing double bonds, and a single covalently grafted fluorinated copolymer network layer. The substrate is then sequentially cleaned with ethyl acetate, ethanol, and isopropanol for 20 minutes each, and the cleaning is repeated twice to remove unreacted monomers, residual initiators, and ungrafted free polymers. The substrate is then vacuum-dried at 40°C for 12 hours to obtain a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold (fluorinated copolymer coating thickness is 5 μm). The thermally initiated monomer composition comprises total monomers, a thermal initiator (AIBN, 0.3% of the total monomer weight), and a solvent (ethyl acetate and ethanol in a volume ratio of 7:3, with a total monomer concentration of 15 wt%). The total monomers are C1-C6 fluoroalkyl methacrylates (TFEMA and TFPMA in a molar ratio of 55:20), biodegradable or hydrolyzable polyfunctional methacrylates (PCLDMA), and post-modifiable functional monomers (MAA) in a molar ratio of 75:15:10.

[0067] Example 2: A thermally initiated in-situ grafted magnesium alloy scaffold with a fluorine copolymer coating, the preparation method of which includes the following steps: (1) The magnesium alloy support substrate (WE43) was electrochemically polished, and then ultrasonically cleaned with ethanol solution, deionized water and ethanol in sequence for 8 minutes each time. After being dried with nitrogen, it was vacuum dried to complete the pretreatment process and obtain the pretreated magnesium alloy support. (2) The pretreated magnesium alloy scaffold obtained in step (1) was placed in an alkaline solution (0.05 mol / L NaOH solution) and subjected to alkaline heat reaction at 60°C for 12 h to form a hydroxylated layer on the surface. It was then washed with deionized water and ethanol in sequence and vacuum dried at 40°C for 4 h to obtain a hydroxylated magnesium alloy scaffold. (3) The hydroxylated magnesium alloy scaffold obtained in step (2) was placed in a carbon-carbon double bond silane coupling agent solution and condensed at 20°C for 180 min. Then it was washed with ethanol and cured at 60°C for 120 min to obtain a magnesium alloy scaffold modified with double bond silane. The carbon-carbon double bond silane coupling agent solution was prepared by the following method: a 0.5 wt% 3-methacryloyloxypropyltriethoxysilane solution was prepared, the solvent being a mixture of ethanol and water with a volume ratio of 90:10, the pH was adjusted to 3.5 with acetic acid, and pre-hydrolyzed for 10 min; (4) The magnesium alloy scaffold modified with double bond silane obtained in step (3) was immersed in the thermally initiated monomer composition for 3 min. After taking it out, it was purged with nitrogen and rotated to load a thin liquid layer on its surface. Then it was placed in a nitrogen-protected environment for thermally initiated free radical in-situ copolymerization (prepolymerized at 40°C for 60 min, and then main polymerized at 60°C for 6 h). The surface double bond silane and monomer underwent thermally initiated free radical in-situ copolymerization. Then it was cleaned with ethyl acetate, ethanol and isopropanol in sequence, each solvent for 10 min, and the cleaning was repeated 3 times to remove unreacted monomers, residual initiators and ungrafted free polymers. It was vacuum dried at 40°C for 12 h to obtain a magnesium alloy scaffold with thermally initiated in-situ grafted fluorine copolymer coating (fluorine copolymer coating thickness is 0.3 μm). The thermally initiated monomer composition comprises total monomers, a thermal initiator (AIBN, 0.01% of the total monomer weight), and a solvent (ethyl acetate and ethanol in a volume ratio of 7:3, with a total monomer concentration of 1 wt%). The total monomers are C1-C6 fluoroalkyl methacrylates (TFEMA and TFPMA in a molar ratio of 55:20), biodegradable or hydrolyzable polyfunctional methacrylates (polycarbonate dimethacrylate), and post-modifiable functional monomers (2-hydroxyethyl methacrylate).

[0068] Example 3: A thermally initiated in-situ grafted magnesium alloy scaffold with a fluorine copolymer coating, the preparation method of which includes the following steps: (1) The magnesium alloy support substrate (WE43) was electrochemically polished, and then ultrasonically cleaned with ethanol solution, deionized water and ethanol in sequence for 8 minutes each time. After being dried with nitrogen, it was vacuum dried to complete the pretreatment process and obtain the pretreated magnesium alloy support. (2) The pretreated magnesium alloy scaffold obtained in step (1) was placed in an alkaline solution (2 mol / L NaOH solution) and subjected to alkaline heat reaction at 120°C for 0.5 h to form a hydroxylated layer on the surface. It was then washed with deionized water and ethanol in sequence and vacuum dried at 80°C for 0.5 h to obtain the hydroxylated magnesium alloy scaffold. (3) The hydroxylated magnesium alloy scaffold obtained in step (2) was placed in a carbon-carbon double bond silane coupling agent solution and condensed at 50°C for 20 min. Then it was washed with ethanol and cured at 120°C for 10 min to obtain a magnesium alloy scaffold modified with double bond silane. The carbon-carbon double bond silane coupling agent solution was prepared by the following method: a 5 wt% vinyltrimethoxysilane solution was prepared, the solvent being a mixture of ethanol and water with a volume ratio of 90:10, the pH was adjusted to 5.5 with acetic acid, and pre-hydrolyzed for 60 min; (4) The magnesium alloy scaffold modified with double bond silane obtained in step (3) was immersed in the thermally initiated monomer composition for 3 min. After taking it out, nitrogen gas was purged and the control film was rotated to load a thin liquid layer on its surface. Then it was placed in a nitrogen-protected environment for thermally initiated free radical in situ copolymerization (prepolymerization at 55°C for 10 min, followed by main polymerization at 75°C for 1 h) to allow the surface double bond silane to undergo thermally initiated free radical in situ copolymerization with the monomer. Then it was cleaned with ethyl acetate, ethanol and isopropanol in sequence, each solvent for 30 min, and the cleaning was repeated twice to remove unreacted monomers, residual initiators and ungrafted free polymers. It was then vacuum dried at 40°C for 12 h to obtain a magnesium alloy scaffold with thermally initiated in situ grafted fluorine-containing copolymer coating (fluorine-containing copolymer coating thickness is 6 μm). The thermally initiated monomer composition comprises total monomers, a thermal initiator (AIBN, 3% of the total monomer weight), and a solvent (ethyl acetate and ethanol in a volume ratio of 7:3, with a total monomer concentration of 60 wt%). The total monomers are C1-C6 fluoroalkyl methacrylates (TFEMA and TFPMA in a molar ratio of 55:20), biodegradable or hydrolyzable polyfunctional methacrylates (polylactic acid dimethacrylate), and post-modifiable functional monomers (N-hydroxysuccinimide methacrylate).

[0069] Comparative Example 1: A fluorine-free coated magnesium alloy stent, the preparation method of which includes the following steps: In step (4), TFEMA and TFPMA are not included, and the rest is the same as in Example 1.

[0070] Test case I. Infrared Detection The chemical structure of the thermally initiated in-situ grafted fluorine-containing copolymer-coated magnesium alloy scaffold prepared in Example 1 was confirmed by Fourier transform infrared spectroscopy, with the bare scaffold material as background. The results are shown in [Figure 1]. Figure 3 .

[0071] Depend on Figure 3 It can be seen that at 3427 cm -1 The broad absorption peak appearing nearby is attributed to the stretching vibration of -OH; at 2961 cm⁻¹ -1 and 2876 cm -1 The peak at 1468 cm⁻¹ is attributed to the CH stretching vibration. -1 and 1384 cm -1 The peak at 1725 cm⁻¹ is attributed to the CH bending vibration; -1 The strong absorption peak at 1238 cm⁻¹ is attributed to the C=O stretching vibration; furthermore, the peak at 1238 cm⁻¹... -1 1203 cm -1 1144 cm -1 and 1066 cm -1 The presence of a distinct absorption peak nearby can be attributed to CF-related vibrations. These characteristic absorption peaks indicate the presence of characteristic structures such as hydroxyl, hydrocarbon, carbonyl, and fluorine-containing groups in the sample, proving the successful construction of a thermally initiated in-situ grafted fluorine-containing copolymer coating on the magnesium alloy surface.

[0072] II. Scanning Electron Microscopy Detection The hydroxylated magnesium alloy scaffold after alkali heat treatment in step (2), the silanized magnesium alloy scaffold with double bonds in step (3), and the thermally initiated in-situ grafted magnesium alloy scaffold with fluorine copolymer coating in step (4) of Example 1 were respectively squeezed and then expanded with a balloon. After expansion, scanning electron microscopy was performed, and the results are shown in the figure. Figures 4-6 .

[0073] Depend on Figures 4-6 It can be seen that the surface of the scaffold treated with alkali heat is significantly rough. After grafting with silane coupling agent, the surface roughness is reduced. After being pressed and stretched, the surface of the magnesium alloy scaffold with thermally initiated in-situ grafted fluorine copolymer coating is smoother than that of the scaffold treated with alkali heat, and no obvious cracks or peeling of the coating are observed. This indicates that the coating of the present invention has good post-expansion integrity, which helps to maintain its anti-corrosion effect.

[0074] III. Quality Loss Detection The thermally initiated in-situ grafted fluorine-coated magnesium alloy scaffold prepared in Example 1, the fluorine-free coated magnesium alloy scaffold prepared in Comparative Example 1, and the bare scaffold were weighed separately, and then immersed in PBS solution (pH=7.4). The scaffolds were dried and weighed after 7 and 14 days, respectively, and the percentage of mass loss was calculated. The percentage of mass loss was calculated as (dry weight before immersion - mass after immersion with surface residue removed and dried to constant weight) / dry weight before immersion × 100%. The results are shown in Table 1.

[0075] Table 1. Mass loss of stent in Example 1, Comparative Example 1, and bare stent.

[0076] Table 1 shows that the bare stent lost approximately 9.6% of its mass after 7 days, exhibiting significant corrosion product adhesion and localized darkening and roughening of the stent surface. The stent prepared in Example 1 lost approximately 2.7% of its mass, with the coated stent maintaining a relatively intact overall structure, showing only minor localized corrosion or deposits, and no significant coating peeling or structural damage. The bare stent lost approximately 24.8% of its mass after 14 days, exhibiting severe corrosion, a large amount of corrosion products covering the surface, and a decline in localized structural integrity. The stent prepared in Example 1 lost approximately 6.9% of its mass, showing slight localized corrosion and surface roughening, without significant breakage, collapse, or large-area coating failure. The mass loss of the scaffold in Comparative Example 1 after 7 and 14 days was approximately 7.5% and 19.4%, respectively, which was lower than that of the bare scaffold (9.6% and 24.8%). This indicates that the coating formed by silane coupling and non-fluorinated copolymer components can still reduce the corrosion degradation rate of magnesium alloy scaffolds to a certain extent. However, its mass loss was significantly higher than that of Example 1 (2.7% and 6.9%), indicating that the introduction of fluorinated methacrylate monomers can further enhance the hydrophobic barrier effect of the coating, reduce the penetration of moisture and corrosive ions into the magnesium alloy matrix, and thus more effectively delay the degradation of magnesium alloy scaffolds.

[0077] IV. Cell Culture with Sample Extract The thermally initiated in-situ grafted fluorine-containing copolymer coated magnesium alloy scaffold prepared in Example 1, the fluorine-free coated magnesium alloy scaffold prepared in Comparative Example 1, and the bare scaffold were respectively subjected to cell culture experiments using sample extracts. The specific experimental methods were as follows: Under conditions of 37°C and 5% CO2, the thermally initiated in situ grafted fluorinated copolymer-coated magnesium alloy scaffold prepared in Example 1, the fluorine-free coated magnesium alloy scaffold prepared in Comparative Example 1, and the bare scaffold were extracted with 1 mL of serum-free DMEM (Dürbeco modified Eagle medium) for 24 h. After extraction, the supernatant was collected and stored at 4°C for subsequent cell culture. Endothelial cells were cultured at a rate of 1 x 10⁻⁶ cells / mL. 4 cells / cm 2 The sample was pre-seeded at a density in blank plates and incubated for 1 day in a cell culture incubator. The original culture medium in the plates was discarded, and sample extract was added, followed by incubation for another day in a cell culture incubator. The plates were then removed, the liquid in the plates was discarded, and 350 μL of CCK-8 reagent (CCK-8 to culture medium volume ratio of 1:9) was added in the dark. The plates were incubated in a cell culture incubator for 3 hours. Subsequently, 200 μL of supernatant was aspirated from each well and transferred to a 96-well plate, and the absorbance at 450 nm was measured using a microplate reader. The results are shown below. Figure 7 .

[0078] Depend on Figure 7 It can be seen that the absorbance value of endothelial cells cultured in the scaffold extract of Example 1 is higher than that of the bare scaffold, indicating that the fluorinated copolymer coating can effectively slow down the degradation of magnesium alloy, thereby reducing the cytotoxicity of degradation products and exhibiting good cell compatibility. The results of Example 1 are slightly higher than those of Comparative Example 1, mainly because the soaking time is only one day. If the soaking time is extended, the results of Example 1 will be significantly higher than those of Comparative Example 1.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a thermally initiated in-situ grafted magnesium alloy scaffold with a fluorinated copolymer coating, characterized in that, Includes the following steps: (1) The magnesium alloy support substrate is pretreated to obtain a pretreated magnesium alloy support; (2) The pretreated magnesium alloy scaffold obtained in step (1) is placed in an alkaline solution for alkaline-thermal reaction, then cleaned and dried to obtain a hydroxylated magnesium alloy scaffold. (3) The hydroxylated magnesium alloy scaffold obtained in step (2) is placed in a carbon-carbon double bond silane coupling agent solution to carry out a condensation reaction, and then cleaned and cured to obtain a double bond silane modified magnesium alloy scaffold. (4) The magnesium alloy scaffold with double bond silane modified in step (3) is immersed in the thermally initiated monomer composition to load a thin liquid layer on its surface. Then, thermally initiated free radical in-situ copolymerization is carried out, followed by cleaning and drying to obtain a thermally initiated in-situ grafted fluorine copolymer coated magnesium alloy scaffold. The thermally initiated monomer composition consists of total monomers, thermal initiators and solvents. The total monomers are C1-C6 fluoroalkyl methacrylates, degradable or hydrolyzable polyfunctional methacrylates and post-modified functional monomers.

2. The method for preparing a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold according to claim 1, characterized in that, In step (1), the surface roughness Ra of the pretreated magnesium alloy support is 10 nm-300 nm.

3. The method for preparing a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold according to claim 1, characterized in that, In step (2), the alkaline solution is at least one of NaOH solution, KOH solution and LiOH solution.

4. The method for preparing a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold according to claim 1, characterized in that, In step (2), the alkaline heat reaction is carried out at 60℃-120℃ for 0.5h-12h.

5. The method for preparing a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold according to claim 1, characterized in that, In step (3), the carbon-carbon double bond silane coupling agent is 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane or allyltriethoxysilane.

6. The method for preparing a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold according to claim 1, characterized in that, In step (3), the condensation reaction is carried out at 20℃-50℃ for 20min-180min.

7. The method for preparing a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold according to claim 1, characterized in that, In step (4), the C1-C6 fluoroalkyl methacrylate is at least one of 2,2,2-trifluoroethyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, and 2,2,3,3,4,4,5,5-octafluoropentyl methacrylate; the degradable or hydrolyzable polyfunctional methacrylate is at least one of polycaprolactone dimethacrylate, polycarbonate dimethacrylate, polylactic acid dimethacrylate, acetal dimethacrylate, disulfide dimethacrylate, succinate dimethacrylate, phosphate dimethacrylate, and glycerol dimethacrylate succinate; the post-modifiable functional monomer is methacrylic acid, 2-hydroxyethyl methacrylate, N-hydroxysuccinimide methacrylate, propargyl methacrylate, azidoethyl methacrylate, maleimide methacrylate, or protected amino methacrylate.

8. The method for preparing a thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold according to claim 1, characterized in that, In step (4), when thermally initiated free radical in situ copolymerization is carried out, polymerization is carried out at 40℃-90℃ for 0.5h-12h.

9. A thermally initiated in-situ grafted magnesium alloy scaffold with a fluorinated copolymer coating, characterized in that, The scaffold was prepared by the method described in any one of claims 1-8, which involves thermally initiated in-situ grafting of a fluorinated copolymer-coated magnesium alloy scaffold.

10. The application of the thermally initiated in-situ grafted fluorinated copolymer coated magnesium alloy scaffold according to claim 9 in the preparation of magnesium alloy scaffolds.

Citation Information

Patent Citations

  • Anti-fouling coating with anticoagulation and / or in-situ endothelialization function as well as preparation method and application of anti-fouling coating

    CN118615497A

  • Corrosion-resistant collagen-functionalized magnesium-based metal coating and preparation method thereof

    CN121059912A